ANALISIS MODEL KEPEMIMPINAN KEPALA DINAS PARIWISATA KABUPATEN GUNUNGKIDUL DALAM KEBERHASILAN PROGRAM PASAR DIGITAL - Dyah Indriyaningsih Septeri; Mustakina, Debi; Setyawati, Dewi; Maulida, Latifah; Sugiyanti, Tri (STISIP Widyapuri Mandiri Sukabumi, 2024)
The Digital Market Program is part of the Quick Wins Smart City initiative which aims to promote tourist destinations through digital media. The success of the Digital Market Program in Gunungkidul Regency is influenced by the leadership role of the Head of the Tourism Service. This research aims to analyze the leadership model of the Head of the Gunungkidul Tourism Service in the success of the program. The research method used is descriptive qualitative with primary and secondary data sources obtained from observation, interviews and documentation. Meanwhile, the technique for determining informants uses purposive sampling. The research results show that the leadership model used is transformational leadership. Heads of departments demonstrate ideal influence with consistent translation of vision and mission, intellectual stimulation through digital innovation, individual attention to staff development, and inspirational motivation through symbolic programs. Although there are aspects of charismatic and transactional leadership, the transformational approach is dominant and effective in facing the challenges of the digitalization era of tourism. To strengthen the success of the Digital Market Program, it is recommended that department heads increase technology-based training for staff, expand cross-sector collaboration in digital innovation, and ensure program sustainability through regular evaluations and strategy adjustments according to technological developments and tourist needs.